A child protection issue: Exploring the causes of school-based violence in South Africa from a bio-ecological systems perspective - Sipho Sibanda; Poppy Masinga (Child Protection and Practice)
Background: School based violence in South Africa has severe consequences for learners, families, educators, and the entire community. Being aware of the complex causes of violence in schools enables social workers and other service providers to respond effectively through well targeted interventions and services. Objectives: The article explores the causes of school-based violence in South Africa from a bio-ecological systems perspective. Participants: and setting: The study was conducted at nine high schools in South Africa. 47 grade 9 and 10 learners and 30 educators participated in the study. Methods: Using a qualitative case-study design, data was collected from learners and educators through focus group discussions and analysed using thematic analysis. Measures were put in place to ensure the quality of data. Findings: The findings indicate that school-based violence is caused by several intersecting factors which include individual-factors such as learner indiscipline; family-related factors such as poverty; inter-personal factors such as peer pressure and status; provocation and revenge; gambling; community-related factors such as the prevalence of gangsterism; alcohol and drugs in communities; school-related factors such as the unprofessional behaviour of educators; and structural factors such as racism and prejudice. Conclusions: Violence in South African schools should be declared a child protection issue caused by multiple interacting individual, family, group, community, and socio-economic historical factors. The design of a comprehensive school-based violence prevention programme guided by the bio-ecological systems perspective is recommended to address the complex causes of school-based violence as a way of safeguarding the rights and wellbeing of school-going children.